دور التوجه السوقي في الحد من الخداع التسويقي: بحث استطلاعي لآراء عينة من زبائن المتاجر الافتراضية - محمود، ناجي عبدالستار; حمادي، أحمد عباس (جامعة تكريت - كلية الإدارة والاقتصاد, 2021)
The aim of the research is to know the relationship and influence between market orientation and marketing deception, and the research relied on the descriptive analytical approach in presenting and discussing data, as the method works on coupling the description of the case with its analysis and drawing conclusions related to it. For the purpose of collecting the required data to solve the research problem, a questionnaire was used, which was distributed to a sample of (140) customers of virtual stores, from which (100) valid questionnaires were retrieved for statistical analysis, and through the use of the statistical analysis program (SPSS v.25), the data of the practical side were analyzed Which included an analysis of the answers and opinions of the respondents, as well as a test of the research hypotheses, and a set of conclusions was reached, the most important of which are: There is a significant (inverse) correlation between market orientation and at the dimensional level with marketing deception, meaning the greater the market orientation of virtual stores, the less deception marketing.
هدف البحث إلى معرفة العلاقة والتأثير بين التوجه السوقي والخداع التسويقي، واعتمد البحث على المنهج الوصفي التحليلي في عرض البيانات ومناقشتها، إذ يعمل المنهج على اقتران وصف الحالة بتحليلها واستخلاص النتائج الخاصة بها. ولغرض جمع البيانات المطلوبة لحل مشكلة البحث استخدمت الاستبانة التي وزعت على عينة قدرها (140) زبونا من زبائن المتاجر الافتراضية أسترد منها (100) استبانة صالحة للتحليل الإحصائي، ومن خلال استخدام برنامج التحليل الإحصائي (SPSS v.25)، تم تحليل بيانات الجانب العملي الذي تضمن تحليل لإجابات وآراء الزبائن المبحوثين، فضلا عن اختبار لفرضيات البحث، وقد تم التوصل إلى مجموعة من الاستنتاجات من أهمها: وجود علاقة ارتباط معنوية (عكسية) بين التوجه السوقي وعلى مستوى الأبعاد مع الخداع التسويقي بمعنى كلما زاد التوجه السوقي للمتاجر الافتراضية كلما قل الخداع التسويقي.
Keywords: التجارة الإلكترونية -- حماية المستهلك -- الغش التجاري -- إدارة التسويق